Pinus caribaea var. hondurensis Wood Impregnated with Methyl Methacrylate - Stolf, Denise Ortigosa; Bertolini, Marilia da Silva [UNESP]; Christoforo, Andre Luis; Panzera, Tulio Hallak; Moni Ribeiro Filho, Sergio Luiz; Rocco Lahr, Francisco Antonio (Asce-amer Soc Civil Engineers, 2017)
This paper investigates the normal hardness, the compressive strength, and the modulus (parallel to the grain) of Pinus caribaea var. hondurensis wood in pristine condition and impregnated with methyl methacrylate (MMA) in autoclave at 0.22 and 0.66 MPa. An artificial weathering over a period of 2,400 h was used to better assess its effect upon the mechanical properties of impregnated wood. The analysis of variance identified that MMA impregnation significantly affected the responses; in contrast, no effect was verified by the artificial aging factor. Treated Pinus wood at 0.66 MPa achieved superior mechanical properties compared with the pristine condition, revealing percent increases in compressive strength, stiffness, and hardness of 84, 36, and 347%, respectively. The scanning electron microscopy (SEM) analysis revealed the MMA polymer was able to fill the wood pores completely. Possibly, impregnated Pinus wood can be used in structural applications in civil construction, in addition to being a low-cost specie in comparison to the typical high-density wood commonly used. (C) 2016 American Society of Civil Engineers.
Keywords: Polymer-matrix composites (PMCs); Wood; Mechanical properties; Autoclave; Artificial weathering